KEADILAN SOSIAL DALAM TANTANGAN EKONOMI PASAR. Mencermati Gagasan Keadilan Sosial Hayek - Andre Ata Ujan (Institut Filsafat dan Teknologi Kreatif Ledalero, 2013)
Is social justice or economic justice a utopia? This would be one of the questions that anyone might immediately raise as he/she reads Friedrick August von Hayek’s position on the idea of social or economic justice. As a classic liberal thinker, Hayek believed that the free market is the ideal economic system for it in nature promotes freedom and equality in a free and open society. Is Hayek’s defence of the free martket economy sufficiently convincing to eliminate any room for social or economic justice to take place? There is actually no free market in a pure sense. The market is not totally free from selfish interests that might be developed by market players themselves in doing business. It is therefore not reasonable to see the market as a purely spontaneous and independent entity. And since it is in fact open to selfish interventions, its outcomes may be just or unjust. Free competition, prompted systematically by the free market system, therefore, could risk human life. For this reason, state intervention to a certain extent is necessary to prevent market competition from endangering citizens’ economic prospects. The state’s intervention is important, as it is necessary, to secure social or economic justice. Social or economic justice is of course an ideal but not necessarily a utopia in a radical sense. Taking the unfortunates’ quality of life as the benchmark in designing and enacting economic policies, social or economic justice might be, at least partially, realized. John Rawls’ idea of maximin rule or maximin strategy can pave the way for the realization of such an ideal that every civilized person or society is essentially craving for. Kata-kata Kunci: Kebebasan, pasar bebas, katalaksi, spontan, impersonal, hukum, keadilan sosial, ekonomi komando, regulasi, maximin rule.